ECONOMIC EFFICIENCY OF VARIOUS TECHNOLOGIES OF GRAIN PRODUCTION - V. B. Rykov; S. I. Kambulov; I. A. Kambulov; N. V. Shevchenko; S. D. Ridny; A. S. Popov (Зерновое хозяйство России)
The article deals with the opportunities and results of the study of winter wheat cultivation with the different technologies in the conditions of insufficient and unstable humidity of the south of Russia. The experiments have been carried out in the conditions of stationary trials in the four crop rotation sequences with different variants of tillage (moldboard, subsoil), including the variants without plowing. The calculation of economic efficiency includes the definition of the labor costs per 1 ha of sowing and per 1 hwt of products, a relative amount of investments, fuel consumption, maintenance costs and the prime cost of production, etc. The use of the zero tillage (no-till farming) to the production of winter wheat provides the labor cost of 7213.6 p-p; maintenance costs of 5934.9 th rub; fuel consumption of 36.1 t per 1000 ha that is 11-21, 66-87 and 97-142% less (respectively) in comparison with the other mentioned technologies of winter wheat production. The analysis of the system of costs shows that they are practically similar for all mentioned technologies in the periods of crop tending and harvesting. The main difference in the fuel consumption, labor costs and investments are substantiated by the amount of work in the main tillage. More than a half of all maintenance costs are the expenditures on the renovation (remodeling), which underlines the high cost of the applied technological means and their low reliability (short period of amortization and large costs of maintenance). The prime cost of winter wheat production with the zero tillage is 212.8 rub/hwt, that is on 31-38% lower in comparison with other cultivation technologies. The cost of plant protection with the zero tillage is more than threefold higher in comparison with other cultivation technologies.